Intensive care in Ancient Egypt through the texts - Fernando Gil González (Universidad de Alicante, 2013)
This article is entitled Intensive care in the Ancient Egypt through the texts. For this reason, they will try to elucidate various aspects of infectious treatments of the Pharaonic period through texts, conducting a comprehensive study on the treatments offered by the Egyptian doctors. To sum up, there will be a parallel between the Ancient Egypt´s Medicine and the current one. Likewise you will defend a particular line of healing (instrumental, palliative, formulas), since ancient times until our days that will only be damaged by the use of the technological applications in the course of time.